Nutritional Intake Predicts Performance in an Ironman Triathlon - Downey, B.; Hopkins, W. (Sportscience, 2001)
The aim of the present study was describe these relationships for one of the most popular of the ultra-endurance events, the Ironman triathlon. Finish time for 59 triathletes in an Ironman triathlon correlated highly with rates of carbohydrate and water intake (r = -0.65 and -0.51). Triathletes with below average intakes of carbohydrate and water can therefore expect to achieve worthwhile reductions in finish time of around 5% from moderate increases in intake.